Perception of pregnant women in Primary Health Care about healthy eating - Sousa Gomes, Emilli Roberta; Jaques Rodrigues, Eva Lorena; da Silva de França, Camila de Cassia; dos Santos Figueiredo, Sandra Maria; de Oliveira Carvalho Granado Santos, Thaís (O Mundo da Saúde, 2023)
Pregnancy promotes several transformations in the female organism, leading to a greater energetic and nutritional demand. If the demand is not met, there will be a competition between the fetus and the mother, which can cause harm to fetal development. Although widely discussed, it is not very clear how pregnant women see healthy eating and whether they can follow it during their daily life. Therefore, it is important to know how pregnant women understand this theme, whether they are receiving guidance, what they do with the acquired knowledge, and what factors are influencing their dietary choices. The aim of this study was to verify the knowledge of pregnant women assisted in primary health care in Belém, PA concerning healthy eating, such as characterizing the socioeconomic and demographic profile and nutritional status of the participants. This is a quantitative-qualitative study conducted with 27 pregnant women enrolled at MHC Guamá using a questionnaire with socioeconomic and demographic data and a semi-structured form with questions about their perception of healthy eating and self-declared weight, height, and gestational age. Qualitative data were analyzed using the Similitude Analysis and Word Cloud methods. The study pointed out that most pregnant women are young, have a high school education, are single, have one minimum wage income, and know how to achieve a healthy diet. However, several factors influence their food choices such as the conditions of their food, nutrition, and health, and the access and consumption of healthy foods on a daily basis. Regarding nutritional status, the same percentage of eutrophic and overweight pregnant women was observed, which may be related to the various factors that influence their dietary choices.